ANALISIS PENGGUNAAN INPUT TERHADAP PRODUKTIVITAS USAHATANI SAYURAN DI DESA LAMBUSA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Fitri Hendriani; Anas Nikoyan; La Ode Kasno Arif; La Nalefo (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The objective of this study is to ascertain the impact of input utilization on the productivity of kale vegetable cultivation in Lambusa Village, Konda Subdistrict, South Konawe District. The research population consisted of all vegetable farmers in Lambusa Village who cultivated kangkong plants, amounting to a total of 120 individuals. The sample was selected using a proportional random sampling technique, with 30% of the total population allocated to the sample, resulting in a sample size of 36 respondents. The sampling technique employed was simple random sampling. This research employs a quantitative methodology. Data were collected through observation, interviews, and document analysis with the assistance of questionnaires, which were administered via the media. The variables under investigation in this study are productivity and input usage. In this study, a quantitative descriptive analysis was employed. The formulas utilized in this study include the productivity formula, which was employed to ascertain the level of vegetable productivity, and the Coob-Douglas function analysis formula, which was utilized to determine the impact of input utilization on productivity. These calculations were conducted with the assistance of the SPSS 26 software. The results demonstrated that the average productivity of kale vegetables in Lambusa Village, Konda District, South Konawe Regency was 1.83, with a maximum yield of 2.5 kg/ha and a minimum yield of 1.25 kg/ha. It is evident that input use exerts an influence on production. Based on the six factors identified, it can be posited that five of them, namely land area (X1), seeds (X2), manure (X4), pesticides (X5), and labor (X6), have a significant impact on production. Conversely, the application of urea fertilizer (X3) has been found to have a negligible effect.